Selection of Gd2(WO4)3:Tb3+ for inproving color deviation in white light-emitting diodes - Dieu An Nguyen Thi; Nguyen Doan Quoc Anh; Phan Xuan Le (Indonesian Journal of Electrical Engineering and Computer Science, 2022)
This study successfully using the hydrothermal technique to synthesize Gd2(WO4)3:Tb3+ phosphors when subjected to calcination under the temperature of 900°C. Here are some aspects that were thoroughly examined: the crystal formation, photoluminescence, photoluminescence excitation, as well as fluorescent degradation for the samples. The (Gd2-xTbx)(WO4)3 (x=0.01-0.15) phosphors exhibit a bright discharge of green under 547 nm (5D4→7F5 shift for Tb3+) when excited at 270 nm (4f8→4f75d1 shift for Tb3+). Because of the exchange interaction between Tb3+, the quenching concentration was determined to be around 10%. The addition of Tb3+ had no effect on the (Gd2-xTbx)(WO4)3 phosphors' CIE chromaticity coordinates (~0.33±0.02, ~0.60±0.02) or color temperatures (~5542 K). Nevertheless, when the Tb3+ content increased, the fluorescence lifespan for 547 nm emission reduced due to energy transfer between Tb3+. The strong green emission from Gd2(WO4)3:Tb3+ phosphors is a potential element for WLEDs and display areas.